Dermal Matrices and Bioengineered Skin Substitutes. Issue 1 (January 2015) - Debels, Heidi; Hamdi, Moustapha; Abberton, Keren; Morrison, Wayne
<x xml:space="preserve">Abstract</x> Background: Over recent decades, scientists and surgeons have collaborated to develop various bioengineered and synthetic products as an alternative to skin grafts. Despite the numerous articles and reviews written about dermal skin substitutes, there is no general consensus. Methods: This article reviews dermal skin scaffolds used in clinical applications and experimental settings. For scaffold evaluation, we focused on clinical and/or histological results, and conclusions are listed. Explanations for general trends were sought based on existing knowledge about tissue engineering principles and wound healing mechanisms. Results: Decellularized dermis seems to remain the best option with no other acellular scaffold being clinically proven to gain better results yet. In general, chemically cross-linked products were seen to be less effective in skin tissue engineering. Biocompatibility could be enhanced by preseeding substitutes with fibroblasts to allow some natural scaffold remodeling before product application. Conclusions: Skin substitutes are a useful tool in plastic and reconstructive surgery practices as an alternative to skin grafts. In the choice of substitute, the general plastic surgery principle of replacing like tissue with like tissue seems to be still standing, and products most resembling the natural dermal extracellular matrix should be preferred.